Legal Responsibilities of Transportation Organizers for Passenger Protection - Kemmala Dewi; Aris Krisdiyanto (Yayasan Adra Karima Hubbi, 2026)
Background. This research is motivated by the increasing public demand for transportation services that guarantee safety, comfort, and fairness, along with high mobility and the rapid development of land, sea, and air transportation. Purpose. This research aims to examine the forms of legal responsibility of transportation operators in protecting passengers and assess its implementation based on the experiences and perceptions of service users. Method. The approach used is qualitative with data collection techniques through interviews and exploration of the views of passengers as key informants. Data are analyzed descriptively and analytically to identify patterns of responsibility, dispute resolution procedures, and the level of perceived effectiveness of legal protection. Results. Research findings indicate that while legal instruments provide a sufficient basis for protection, practical barriers to compensation and access to dispute resolution mechanisms remain. Conclusion. Therefore, strengthening oversight functions, increasing service transparency, and optimizing the complaints system are necessary to ensure transportation operators' legal responsibilities are met effectively and fairly.